الاعتراف بالإيراد في العقود طويلة الأجل في ظل النظام المحاسبي المالي (scf) والمعيار الإيراد من العقود مع العملاء (ifrs15) دراسة حالة شركة باهي للإنجاز والتجهيز -الوادي- - زيدان, يوسف; ضويفي, حمزة (جامعة الوادي - University of Eloued, 2022)
This study aims to demonstrate the compatibility of the accounting treatment for long-term contracts in the accounting system, especially with regard to the methods of revenue recognition with the accounting standard (IFRS15). Revenue from contracts with clients. The study concluded that the recognition of long-term contract revenue is according to two methods: the percentage of progress in completion method, the method Complete contracts, each of which has its effects on the accounting result, as for the extent of compatibility with the accounting standard No. (IFRS15), the study concluded that the national accounting practice did not keep pace with the international accounting developments arrived at in the standard (IFRS15) and this would affect the quality of accounting information
Recognition of revenue in long-term contracts under the Financial Accounting System and IFRS15 Revenue from Contracts with Customers Case Study of Bahi Company -ELOUED-
مقال
Keywords: النظام المحاسبي المالي، العقود طويلة الأجل، المعيار ( IFRS15 )، الإيراد.; financial accounting system, long-term contracts, IFRS15, revenue